Arbeitsmarkt 2030 - Wirtschaft und Arbeitsmarkt im digitalen Zeitalter Prognose 2016 - Vogler-Ludwig, Kurt (W. Bertelsmann Verlag, 2016)
"The third long-term forecast by Economix estimates the implications of the recent influx of refugees on the German labour market as well as the qualification structure among the employees. At the same time, it forecasts the opportunities and risks of digitalisation. All analyses come to the conclusion that the integration of refugees into the labour market represents the primary task of the coming five to ten years. Indeed, the immigration of refugees rejuvenates the population. However, it also causes a decline in the qualification structure of labour supply. The authors emphasise both the necessity of extensive and systematic further education programs for all employees as well as the importance of developing educational services for refugees and encouraging them to participate in vocational education. The digitalisation scenario shows considerable increases in growth and employment as a consequence of the use of digital technologies. However, this positive development requires